Параметры сверхпроводящих магнитных систем с удерживающими элементами внутри тороидального объема - Васецкий, Ю.М.; Мазуренко, И.Л.; Павлюк, А.В. (Технічна електродинаміка, 2011)
On the basis of an idealized model of magnetic systems in form of a toroidal current sheet a parametric analysis of superconducting magnetic energy storage is carried out. The parametric analysis includes the investigation of storage size, the necessary volumes of superconducting windings and mechanical support system. The systems with spokes placed inside each discrete simple circular and segmental shape magnet coils are examined. The spoke system can solve two mechanical problems without resort to the more complicated and expensive "D"-shaped coil geometry, namely: eliminating bending moments in the support system and ensuring uniform mechanical stress in all the spokes and supporting structure. The lowest values of the radial dimensions of toroidal solenoids and the necessary volume of the superconducting material is achieved in systems with segmental shape coils and for the last parameter approaching to the theoretical limit, which occurs in systems with D-shaped coils.